Budaya Kerja: Faktor Penentu Kinerja Karyawan Melalui Variabel Intervening Kepuasan Kerja Dan Komitmen Afektif Pada PT Jasa Asuransi Indonesia (Persero) Cabang Serang - Wibowo, Cokorda Agung; Prahiawan, Wawan; Kambara, Roni (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2020)
PT Jasa Asuransi Indonesia (Persero) builds a corporate culture of "RAISE" as values that are believed, carried out and become the daily behavior and habits of all Jasindo people. This study aims to determine the application of "RAISE" work culture and its effect on employee performance through two intervening variables, job satisfaction and affective commitment. The research object was the employees of PT Jasa Asuransi Indonesia (Persero) Cabang Serang, totaling 42 people. The sampling technique uses saturated sampling. Data analysis used a PLS-based SEM approach. Based on the hypothesis test at the 10% significance level, the results of work culture have a negative and insignificant effect on employee performance. Work culture has a positive and significant effect on job satisfaction and affective commitment. Job satisfaction has no effect on employee performance, while affective commitment has a positive effect on employee performance. This study found an indirect effect of work culture on employee performance through affective commitment as an intervening variable.